Recent Publications (Quarterly Journal of Economics, 1945)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 59, Issue 2, February 1945, Pages 304–306, https://doi.org/10.1093/qje/59.2.304 Published: 01 February 1945